A novel coarse and fine control algorithm to improve Maximum Power Point Tracking (MPPT) efficiency in photovoltaic system. (February 2022) - M., Kavya; S., Jayalalitha
Abstract: The Perturb and Observe (P&O) Maximum Power Point Tracking (MPPT) algorithm in solar Photovoltaics (PV) is popular owing to its simplicity. However, its drawbacks, (i) operating point divergence and (ii) tradeoff between fast convergence and balanced state oscillations decelerate the usage. Most of the developments in the literature to overcome these drawbacks increase complexity. To retain simplicity and also to improve tracking efficiency, this paper proposes a Coarse and fine control algorithm. This proposal has distinct aspects, having three control modes. Mode 1 and 2 enhance fast convergence and mode 3 controls stable state oscillations. The comparative analysis from simulation proves that the proposed technique has fast convergence, reduced balanced state oscillations, better tracking efficiency, and minimum transient power loss than the other techniques. Highlights: Coarse and fine control MPPT algorithm is proposed which is unique in its approach. It splits tracking process into three facets with three control modes. Selection of apt mode is through nonstop intelligent checks. Mode 1 and 2 for coarse control, Mode 3 for fine control. Results confirm the superiorities of proposed algorithm.